Correction: Environmental protection tax and green innovation of heavily polluting enterprises: A quasi-natural experiment based on the implementation of China's environmental protection tax law. - Juqiu Deng; Jiayu Yang; Zhenyu Liu; Qingyang Tan (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0286253.].